Case report: a rare case of primary hyperparathyroidism due to an intrathymic ectopic parathyroid adenoma incidentally diagnosed in a 15-year-old girl - Gurluler, Ercument (Frontiers in Endocrinology, 2024)
Primary hyperparathyroidism (PHPT) due to ectopic parathyroid adenoma is a rare cause of hypercalcemia in the pediatric population. Herein, a rare case of PHPT due to ectopic intrathymic parathyroid adenoma was described in an asymptomatic 15-year-old girl who had incidental diagnosis based on laboratory abnormalities but experienced a 3-month postoperative course of persistently elevated parathyroid hormone (PTH) and hypercalcemia following the initial unsuccessful parathyroidectomy operation carried out in a non-parathyroid expert center. The curative surgical treatment was accomplished only after the patient was reoperated with video assisted thoracoscopic surgery (VATS) thymectomy by the surgeon experienced in parathyroid surgery with implementation of the combined imaging modalities for accurate localization of ectopic adenoma including 99mTc-sestamibi (MIBI) plus neck and thoracic computed tomography (CT) and the appropriate surgical strategies including intraoperative intact PTH monitoring and frozen section diagnosis. Before the reoperation (VATS thymectomy), laboratory findings showed elevated PTH (1171 ng/L; reference range: 21.80-87.5 ng/L) and hypercalcemia (13.4 mg/dL; reference range: 8.4-10.2 mg/dL). The per-operative PTH levels were 94 ng/L at 5 minutes after thymectomy and 78 ng/L at 10 minutes. PTH and calcium levels were 54.3 ng/L and 8.47 mg/dL, respectively on the postoperative day 1, and were 34.2 ng/L and 8.1 mg/dL on the postoperative day 2. Patient was discharged on postoperative day 2 without any complications. In conclusion, our findings indicate the likelihood of isolated primary hyperparathyroidism to be incidentally diagnosed based solely on laboratory abnormalities with no specific clinical manifestations in the pediatric age. In addition, using combined imaging modalities (such as MIBI and CT) in accurate localization of ectopic parathyroid adenoma and implementation of surgery by experienced surgeons along with intraoperative intact PTH monitoring and frozen section diagnosis seem crucial to ensure the curative surgical treatment.